Effects of hydrodynamical regime on morphological evolution at Cua Dai estuary and coastlines of Quang Nam province - Dinh, Cham Dao (Vietnam Journal of Earth Sciences, 2020)
In recent years, accretion-erosion processes are frequently recorded in the estuary of Cua Dai, Quang Nam province. Most recently, however, sand bars are formed in the estuary not far from the place where the Inland Waterways Authority of Vietnam had previously dredged. The estuary continues to be accreted by sand. These have been drawing special attention of national and international scientists. While there is accretion at the estuary, eroded processes are strongly recorded along the coastlines of Quang Nam province. Therefore, it is necessary to carry out a study in the effects of the hydrodynamic regime on morphological changes in the Cua Dai estuary and coastlines of Quang Nam province. The goal of this paper is to fully interpret the causes, regimes of accretion and erosion processes over the study area. In this study, satellite images and hydrodynamic models of Delft3D and MIKE 11 are applied. The results show a strong accretion process in the estuary of Cua Dai. Sandbar formation across the Cua Dai estuary comes from the interaction of flood, wave, and current conditions during the northeast monsoon. This mainly affects the changes in morphology in the estuary of Cua Dai, Quang Nam.